Peningkatan Kemampuan Mengenal Angka Menggunakan Kartu UNO Pada Anak Tunarungu Kelas I SLB-B YPPLB Makassar - As Sa’diyah, Zahra Al-jamil; Mustafa, Mustafa; Zulfitrah, Zulfitrah (Primera Educatia Mandalika: Elementary Education Journal, 2024)
The problem in this research is that grade 1 deaf children with the initials A are less able to recognize numbers, especially indicating and arranging numbers sequentially or randomly at SLB-B YPPLB Makassar. The aim of this research is to determine: 1) the ability to recognize numbers before using UNO card media, 2) the ability to recognize numbers after applying UNO card media, 3) the use of UNO cards can improve the ability to recognize numbers in class I deaf students at SLB-B YPPLB Makassar . This research approach is quantitative with descriptive research type. The data collection technique used was an action test of indicating and writing numbers 0 to 9. This technique was used to measure students' ability to recognize numbers. The test was carried out twice, namely the initial test before using the UNO card media and the final test after using the UNO card media. The conclusions of this research are: 1) the ability to recognize numbers before using UNO card media is included in the less capable category, 2) the ability to recognize numbers after using UNO card media is included in the very capable category, 3) the use of UNO cards can improve the ability to recognize numbers as proven by increasing student abilities from the initial test and final test.